2022
DOI: 10.1039/d2cc02298b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine PtCoRh nanorods for highly efficient hydrogen evolution reaction in acid

Abstract: PtCoRh nanorods with an average width of 1.6 ± 0.2 nm show an overpotential of 6.1 mV at 10 mA cm-2 toward acidic HER. The exceptional activity originates from a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…4–7 In the group investigated thus far, Pt-based materials have been found to possess superior H adsorption properties that make them the most efficient catalyst for the cathodic hydrogen evolution reaction (HER). 8–10 However, it is commonly observed that the alkaline seawater splitting performance of Pt-based catalysts is substantially lower than that in alkaline media, primarily owing to chloride ion-promoted corrosion associated with metal chloride/hydroxide formation (eqn (1)–(3)). 11–13 This highlights an urgent need for new strategies to design high-performance and durable Pt-based electrocatalysts for seawater HER.Pt + Cl − → PtCl ads + e − PtCl ads + Cl − → PtCl x − PtCl x + OH − → Pt(OH) x + Cl − …”
mentioning
confidence: 99%
“…4–7 In the group investigated thus far, Pt-based materials have been found to possess superior H adsorption properties that make them the most efficient catalyst for the cathodic hydrogen evolution reaction (HER). 8–10 However, it is commonly observed that the alkaline seawater splitting performance of Pt-based catalysts is substantially lower than that in alkaline media, primarily owing to chloride ion-promoted corrosion associated with metal chloride/hydroxide formation (eqn (1)–(3)). 11–13 This highlights an urgent need for new strategies to design high-performance and durable Pt-based electrocatalysts for seawater HER.Pt + Cl − → PtCl ads + e − PtCl ads + Cl − → PtCl x − PtCl x + OH − → Pt(OH) x + Cl − …”
mentioning
confidence: 99%